Penerapan Pembelajaran Berbasis Web untuk Meningkatkan Pemahaman Konsep dan Keterampilan Generik Sains Siswa Kelas X SMA pada Materi Suhu dan Kalor - Zulkarnaini Zulkarnaini (Jurnal Dedikasi Pendidikan, 2018)
Along with the rapid development of information and communication technology (ICT), the need for an ICT-based concept and mechanism of teaching and learning becomes inevitable. The concept then known as e-learning is bringing the influence of the process of transformation of conventional education into digital form, both content, and system. On the other hand, information technology has become the world's largest computer network, which works well if it is supported by computer devices with good software and with well-trained teachers. Using the internet with all the facilities will make it easy to access various information for education that can directly improve students' knowledge for their success in learning. Likewise in Permendiknas Number 22 of 2006 point, 2 stated that one of the objectives of physics is to develop science and technology. One of the developments of science and technology is the availability of professional teachers. With the results of this study are 1) Application of web-based learning on temperature and caloric materials can improve the concept understanding among students significantly compared with conventional learning methods. 2) The use of web-based technology in the learning process of temperature and heat material can significantly increase students' KGS compared to conventional learning methods. 3) Students give a very positive response to the implementation of web-based learning on temperature and heat materials.